Analisis Komparatif Kinerja Pemasok Kemasan Menggunakan Pendekatan AHP-SAW dan AHP-WP - Martha Herlina Br Sihombing; Vania Sheri Felicia; Cindy Malinda Uscha; Dewi Hajar (Multmedia Nusantara Politeknik, 2026)
This study aims to evaluate the performance of packaging suppliers used by Nasi Tempong Nyonya as a crucial component of operational effectiveness in the fast-food industry. Packaging suppliers play a strategic role in supporting daily operations, as packaging quality directly affects food safety, product presentation, brand image, and overall customer satisfaction. Therefore, systematic supplier evaluation is required to ensure consistent material quality, price stability, timely delivery, and reliability of supply in meeting operational demands. Preliminary observations reveal several challenges in the procurement of packaging materials, including frequent price fluctuations, inconsistent material quality, limited use of environmentally friendly packaging, and suboptimal supplier responsiveness to sudden changes in demand volume. These issues have the potential to disrupt operational workflows and reduce service consistency. To address these concerns, this research adopts an evaluative approach by analyzing key supplier performance indicators, direct operational observations, and assessments aligned with the company’s operational needs and standards. The findings indicate that the current packaging supplier has not fully met Nasi Tempong Nyonya’s operational expectations, particularly in terms of material quality consistency and delivery timeliness. These shortcomings highlight the importance of implementing a more structured and objective supplier evaluation system. Such a system can serve as a strategic basis for performance improvement initiatives, strengthening long-term supplier relationships, or considering alternative suppliers. Ultimately, this study is expected to provide practical insights to enhance operational efficiency and maintain consistent service quality for customers.